2013
DOI: 10.1590/s1676-06032013000100017
|View full text |Cite
|
Sign up to set email alerts
|

Nest architecture of the stingless bee Geotrigona subterranea (Friese,1901) (Hymenoptera: Apidae: Meliponini)

Abstract: Abstract:We located ten nests of Geotrigona subterranea in the transition area between Cerrado and Caatinga within the municipalities of Lontra and Januária, state of Minas Gerais, southeastern Brazil. We collected the nests to study their architecture in detail. In the present paper, we describe the general nest structure of this bee species in terms of: number, shape and area of the combs; size of the brood cells; size of honey and pollen pots; volume of honey and mass of pollen stored in closed pots; presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
2
9
0
2
Order By: Relevance
“…Spiral brood comb was observed in all colonies studied here, corroborating findings reported by Sakagami and Zucchi (1967) and Nogueira-Neto (1970), and can occur in other Meliponini (Laroca, 1971;Wille & Michener, 1973;NogueiraNeto, 1997;Souza et al, 2007;Brito et al, 2012;Barbosa et al, 2013). The population of colonies in Ribeirão Preto was far above the maximum population of 10,000 bees calculated by Tóth et al (2004), possibly due to the different estimation methods.…”
Section: Discussionsupporting
confidence: 89%
“…Spiral brood comb was observed in all colonies studied here, corroborating findings reported by Sakagami and Zucchi (1967) and Nogueira-Neto (1970), and can occur in other Meliponini (Laroca, 1971;Wille & Michener, 1973;NogueiraNeto, 1997;Souza et al, 2007;Brito et al, 2012;Barbosa et al, 2013). The population of colonies in Ribeirão Preto was far above the maximum population of 10,000 bees calculated by Tóth et al (2004), possibly due to the different estimation methods.…”
Section: Discussionsupporting
confidence: 89%
“…We found the occurrence of an involucrum and the resin pile, typical of this species. In the brood area, the involucrum layers keep the temperature by retaining the heat production from brood metabolism (Wille, 1983;Engels et al, 1995;Barbosa et al, 2013). The presence of garbage dump deposit was observed in this study such as previously reported by Nogueira-Neto (1997) in other stingless bee species.…”
Section: Nest and Colony Estimativesupporting
confidence: 87%
“…The fact that average of free acidity in the Ecuadorian Trigona is 609.33 meq/kg should be explained by the species and the interactions of the underground nest with the soil. Behavioral observations of the underground bees and their nests are needed to understand such a different pot-honey [43], and hypothesize the origin of such chemical array. This is a very thin honey with 37.06 g/100 g water content, almost double of the 20% maximum permitted in the Ecuadorian honey norm [25].…”
Section: Discussionmentioning
confidence: 99%